Transformation and Evolution Human Resources: Technology Integration in HR Development - Iing Sri Hardiningrum; Agus Hermawan; Anita Sumelvia Dewi; Erwin Syahputra (Cita konsultindo, 2024)
Highlighting the importance of management source Power inner digital human reach success and sustainability organization, emphasized the necessity of HR leader to align technology with the objective organization in an effective way. The purpose of the study Is To explore integration technology in the development source Power Man through a literature review, emphasizing the evolution management source Power Human on the side progress technology. Study This underlines the importance increase professional skills for utilizing progress technology in a way efficient and digital role in simplifying processes, improving productivity, and enabling more decisions​ automatically in HR development. Research results show that digital technology can reduce and create opportunities Work with culture organizations identified as a barrier to adoption of digital technology in HR management. Implications of digital transformation of HR management strategies are explored to show support in the organization and impact positive technology on internal operations and practices of HR management.